PWM Techniques for Two-Level Voltage Source Inverters: A Comparative Study - Battur Batkhishig; Pedro F. da Costa Goncalves; Giorgio Pietrini; Babak Nahid-Mobarakeh; Ali Emadi (IEEE Access)
Pulse width modulation (PWM) techniques are widely used to control the switching of semiconductors in power converters. This paper presents a comprehensive overview of PWM techniques for two-level voltage source inverters and provides a comparative analysis of commonly employed PWM techniques, including sinusoidal PWM, zero-sequence injection PWM, third-harmonic injection PWM, space vector modulation, and optimized pulse pattern with selective harmonic mitigation. Besides providing a detailed literature review, this study includes multiple experimental results to evaluate the performance of these PWM techniques across different key metrics, such as output power quality, DC-link voltage utilization, dynamic response, and complexity. Given the growing trend of electrification in the transportation sector, particular emphasis is placed on motor drive applications. Furthermore, this paper discusses the impact of digital controllers, wide-bandgap semiconductors, and model predictive control on PWM techniques while addressing the challenges and future trends within this field.